Overcoming a Hurricane and Maintaining Wellness in College Student Physical Education - Lothes II, John E.; Schroeder, Lindsey H.; Chen-Edinboro, Lenis (Building Healthy Academic Communities Journal, 2021)
Background: With instructional time lost due to natural disasters, it is essential to examine the effect of a physical education course (PED 101) on college student well-being and motivation. Aim: This research examines the effect of physical education classes with a wellness component on wellness and motivation during a disruptive hurricane. Methods: A pre and posttest survey methodology was utilized to measure well-being and motivation, including by gender and exercise frequency, using the Wellness Inventory on college students enrolled in PED 101 who experienced Hurricane Florence. Results: All 12 dimensions of participants' wellness and their motivation to make changes in those wellness dimensions increased by the end of the hurricane semester. The results found significant changes between the pre- and post-assessment scores for all dimensions of wellness and motivation for male and female participants, as well as for all levels of exercise frequency. Conclusions: Including a well-being and motivation component in a college level physical education curriculum may enhance students' overall well-being and motivation during a disruptive hurricane.